A New Proof of Hamilton's Theorem on Harmonic Maps from Manifolds with Boundary (Journal of Partial Differential Equations, 1997)
We give a simple proof of the well-known Hamilton's result [1] on the heat flows and harmonic maps from manifolds with boundary using the approach of Ding-Lin [2].
Keywords: Heat flow; harmonic maps